A cosmopolitanism of nations : Giuseppe Mazzini's writings on democracy, nation building, and international relations - Mazzini, Giuseppe, 1805-1872 (Princeton University Press, 2009)
This anthology gathers Giuseppe Mazzini's most important essays on democracy, nation building, and international relations, including some that have never before been translated into English. These neglected writings remind us why Mazzini was one of the most influential political thinkers of the nineteenth century--and why there is still great benefit to be derived from a careful analysis of what he had to say. Mazzini (1805-1872) is best known today as the inspirational leader of the Italian Risorgimento.